2022
DOI: 10.1530/erc-21-0355
|View full text |Cite
|
Sign up to set email alerts
|

Personalized drug testing in human pheochromocytoma/paraganglioma primary cultures

Abstract: Aggressive pheochromocytomas and paragangliomas (PPGLs) are difficult to treat, and molecular targeting is being increasingly considered, but with variable results. This study investigates established and novel molecular-targeted drugs and chemotherapeutic agents for the treatment of PPGLs in human primary cultures and murine cell line spheroids. In PPGLs from 33 patients, including 7 metastatic PPGLs, we identified germline or somatic driver-mutations in 79% of cases, allowing us to assess potential differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Noteworthy, responders included SDHB -mutant patients [ 66 , 70 , 71 ]. This is in accordance with the results of preclinical studies on human PPGL primary cultures that showed significantly stronger efficacy of cabozantinib in cluster 1 tumors, particularly SDHB-mutated, compared with cluster 2 tumors [ 66 , 72 ].…”
Section: Therapeutic Optionssupporting
confidence: 90%
“…Noteworthy, responders included SDHB -mutant patients [ 66 , 70 , 71 ]. This is in accordance with the results of preclinical studies on human PPGL primary cultures that showed significantly stronger efficacy of cabozantinib in cluster 1 tumors, particularly SDHB-mutated, compared with cluster 2 tumors [ 66 , 72 ].…”
Section: Therapeutic Optionssupporting
confidence: 90%
“…When the patient's clinical course and physical condition are intolerable, radionuclide therapy alone, a combination approach with pre-operative embolization or stereotactic body radiotherapy may be used [10] , [11] , [12] . Some novel molecular-targeted drugs include cabozantinib, selpercatinib, everolimus, sunitinib, alpelisib, trametinib, niraparib, and entinostat could be effective treatment options [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they can be easily standardized, and yet, they provide enough complexity, such as 3D geometry, to represent relevant aspects of human tumours [ 38 ]. Spheroids generation facilitates the growth of highly uniform spheroids and allow real-time monitoring of drug-induced changes in their phenotypes [ 27 , 39 , 40 ]. We previously demonstrated that TME, represented by primary CAFs, plays a fundamental and specific role in inducing the invasion properties of spheroid cells and that this effect is extraordinarily enhanced in MTT SDHB sil ones [ 27 ].…”
Section: Discussionmentioning
confidence: 99%